Understanding social action, promoting human rights - Goodman, Ryan.; Jinks, Derek; Woods, Andrew K. (New York : Oxford University Press, 2013)
The editors bring together a stellar group of contributors from across the social sciences to apply a broad yet conceptually unified array of advanced social science research concepts to the study of human rights and human rights law.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Human rights; Sociological jurisprudence